2021
DOI: 10.1038/s41598-021-95706-z
|View full text |Cite
|
Sign up to set email alerts
|

Livestock movement informs the risk of disease spread in traditional production systems in East Africa

Abstract: In Africa, livestock are important to local and national economies, but their productivity is constrained by infectious diseases. Comprehensive information on livestock movements and contacts is required to devise appropriate disease control strategies; yet, understanding contact risk in systems where herds mix extensively, and where different pathogens can be transmitted at different spatial and temporal scales, remains a major challenge. We deployed Global Positioning System collars on cattle in 52 herds in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 38 publications
2
26
1
Order By: Relevance
“…Additionally, the study in the North identified that herders who practised grazing of small ruminants with other animal species reported high FMD contamination. Mixed livestock grazing practice leads to high animal contact and has been reported as a risk factor for FMD spread in west, central, east and southern Africa [32,33,34] and Asia [35] . It has been highlighted that dearth of information on good management practices by herders could be attributed to the disorganized nature of the herders, where only a few of them belong to farmer organizations.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the study in the North identified that herders who practised grazing of small ruminants with other animal species reported high FMD contamination. Mixed livestock grazing practice leads to high animal contact and has been reported as a risk factor for FMD spread in west, central, east and southern Africa [32,33,34] and Asia [35] . It has been highlighted that dearth of information on good management practices by herders could be attributed to the disorganized nature of the herders, where only a few of them belong to farmer organizations.…”
Section: Resultsmentioning
confidence: 99%
“…Illegal livestock incursions into the protected areas could displace wildlife and may account for the negative effects of the hard edges on wildebeest and zebra occupancy. Despite a growing consensus that moderate stocking densities of livestock are compatible with the conservation of native savanna biodiversity (Keesing et al., 2018; Reid, 2012; Sitters et al., 2020; Young et al., 2018), at high densities, livestock have deleterious impacts on native biodiversity by consuming large quantities of the most palatable grass species, suppressing savanna fires and changing the competitive balance between grass, forbs and trees (Sitters et al., 2020; Young et al., 2005) as well as pathogen transmission (Ekwem et al., 2021). Intensive livestock grazing can result in the encroachment of non‐palatable woody species and non‐native plants (Kimuyu et al., 2017) and these changes in the vegetative composition and structure may affect animal movement by presenting different availability of resources and risks (Hopcraft et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Such forays into protected areas present a direct pathway through which wildlife species may be displaced; for instance, herders and their dogs may harass wildlife which may subsequently avoid these areas. Both the agro‐pastoral communities that live along the western boundary of the ecosystem (adjacent to Mbalageti and Tabora transects) as well as the pastoralist Masai communities in the east (adjacent to the Kuka transect) keep moderate to high densities of livestock (Ekwem et al., 2021; Ogutu et al., 2009). Therefore, if livestock incursions were responsible for displacing wildebeest and zebra, then we should observe similar patterns on both the east and west sides, and these effects should be seasonal (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both these systems, livelihoods depend on the ability to move livestock to communal areas to access resources critical for their survival, such as pasture and water 6 . Such movements tend to be local, but they cover variable distances depending on the season, as seasonality in uences resource availability 7 . Livestock movements are also motivated by nancial gains associated with trade along market channels.…”
Section: Introductionmentioning
confidence: 99%